m7G-related genes predict prognosis and affect the immune microenvironment and drug sensitivity in osteosarcoma - Lin, Zili; Wu, Ziyi; Yuan, Yuhao; Zhong, Wei; Luo, Wei (Frontiers in Pharmacology, 2023)
Osteosarcoma (OS), the most prevalent primary malignant bone tumor, exhibited the stagnant therapeutic advancement due to the emergence of multidrug resistance. The onward therapeutic effect requires a further understanding of the occurrence and development of OS. In recent years, m7G, a significant post-transcriptional modification, has garnered increasing attention due to its involvement in various disease processes, particularly cancer. The primary objective of this study was to investigate the role of m7G-related genes in the pathological progression of OS.Bioinformatics analyses were leveraged to explored the molecular landscape of OS by evaluating the contributions of m7G-related genes.Additionally, experimental validations were performed to confirm the expression patterns of m7G-related signatures. As a result, an m7G-related risk model including eight signatures was constructed, and its corresponding risk scores were associated with immune infiltration and drug sensitivity. Through drug sensitivity analysis, we found that AZD2014 may serve as the potentially sensitive drug for OS, and then verified AZD2014 can induce G1-phase cell cycle arrest and apoptosis of OS cells. Finally, we identified CYFIP1 and EIF4A1 as two independent risk factors of OS through multivariate Cox regression analysis and verified the differential expression of CYFIP1 and EIF4A1 at histological and cytological levels, offering new therapeutic targets for OS.